Syndemic of factors that shape the early lives of women who enter into sex work: a qualitative methods study from Nairobi, Kenya - Karen Devries; Helen Anne Weiss; Janet Seeley; Mitzy Gafos; Rupert Kaul; Nambusi Kyegombe; Joshua Kimani; Tara S Beattie; Pooja Shah; Graham F Medley; Rhoda Kabuti; Hellen Babu; et al. (BMJ Open, 2023)
Objective To explore the structural and social co-factors that shape the early lives of women who enter sex work in Nairobi, Kenya.Design Thematic analysis of qualitative data collected as part of the Maisha Fiti study among female sex workers (FSWs) in Nairobi.Participants and measures FSWs aged 18–45 years were randomly selected from seven Sex Workers Outreach Programme clinics in Nairobi and participated in baseline behavioural–biological surveys. Participants in this qualitative study were randomly selected from the Maisha Fiti study cohort and were interviewed between October 2019 and July 2020. Women described their lives from childhood, covering topics including sex work, violence and financial management.Results 48 out of 1003 Maisha Fiti participants participated in the in-depth qualitative interviews. FSWs described how physical and sexual violence, poverty and incomplete education in their childhood and adolescence intertwined with early pregnancy, marriage, intimate partner violence and relationship breakdown in their adolescence and early adulthood. The data analysis found clear syndemic relationships between these risk factors, particularly childhood violence, poverty and incomplete education and highlighted pathways leading to financial desperation and caring for dependents, and subsequent entry into sex work. Women perceived sex work as risky and most would prefer alternative work if possible, but it provided them with some financial independence and agency.Conclusions This is the first study in Kenya to qualitatively explore the early lives of sex workers from a syndemic perspective. This method identified the pivotal points of (1) leaving school early due to poverty or pregnancy, (2) breakdown of early intimate relationships and (3) women caring for dependents on their own. Complex, multi-component structural interventions before these points could help increase school retention, reduce teenage pregnancy, tackle violence, support young mothers and reduce entry into sex work and the risk that it entails by expanding livelihood options.